1998
DOI: 10.1063/1.1148903
|View full text |Cite
|
Sign up to set email alerts
|

Local mechanical spectroscopy with nanometer-scale lateral resolution

Abstract: High speed wafer scale bulge testing for the determination of thin film mechanical properties Rev. Sci. Instrum. 81, 055111 (2010);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Most of these techniques utilize displacement modulation, where either the tip holder or sample is oscillated, and the tip-sample response ͑amplitude or phase shift͒ used to provide an image. [11][12][13][14][15][16][17] In these techniques, the tip can be either in continuous or intermittent contact with the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these techniques utilize displacement modulation, where either the tip holder or sample is oscillated, and the tip-sample response ͑amplitude or phase shift͒ used to provide an image. [11][12][13][14][15][16][17] In these techniques, the tip can be either in continuous or intermittent contact with the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the work of Yuya et al [19], it has been suggested to exploit the Q-value of AFM contact-resonances to perform local internal friction measurements, for example in polymers and relate them to the various relaxation mechanisms, both locally and globally [35]. Similarly, Q-mapping of the contact-resonances of AFM cantilevers has been suggested to image areas of high absorption [36] in materials.…”
Section: Discussionmentioning
confidence: 97%
“…However, the electrochemical strains can be potentially used as the basis for been introduced, in which the SPM probe acts as a highly localized heating element with a low thermal mass (allowing heatingcooling-rates of the order of 10 5 K s − 1 ). Scanning thermal expansion microscopy (SThEM) [ 109 ] and thermally assisted atomic force acoustic microscopy (TA-AFAM) [ 110 ] are two scanning probe techniques, which allow studies of the mechanical properties of the materials as a function of temperature as well as studies of phase transitions with sub-100 nm spatial resolution. In both methods parameters of tip-surface contact resonance as a function of temperature are determined by bringing heated probe in contact with the sample surface.…”
Section: Electromechanical Probesmentioning
confidence: 99%